CURRENT ISSUES OF DIGITIZATION OF TRANSFORMATIONAL PROCESSES IN COMMERCIAL BANKS - Suyunov D. X.; Kaytavov V. R. (American Journals, 2023)
The article analyzes the role of digitization in the transformation of commercial banking activities, the importance, current state and prospects of remote use of banking services. The article also shows the importance and convenience of digitizing the banking sector, the work that should be carried out in this direction Uzbekistan.
Keywords: Banking, digitization, transformation, digital banking, traditional banking, ecosystem, it, online platform.